EMPLOYEE EMPOWERMENT BASED ON COMPETENCY - Elsye Tandelilin (Journal of Management and Business, 2004)
In order to face business competiton that is very complex and the change of external environment that is become very rapid, the firms must do several changes. One of the change is human resource management, because human resource as a trigger which is very important in determining the success of an organization. According to the Sims (2.001) knowledge workers will be the need and the priority of an organization to face the competition and become a thing that we cannot avoided. To have high competence human resource which is appropriate with the need of organization and to be able to manage the organization appropriately will create high valued innovation. An effort to make a condusive condition for the employees in organization so that they can contribute optimally, management team should work harder. Increasing activity of the firm as a result of the change in business environment will make manegement should increase their control on the employees' activities. The consequence is the increase in cost and employee's number. To anticipate that problem, there are many organizations start to use employee empowerment concept. More detail, this concept said that employee empowerment means encouraging and allowing human resource (employees) to be responsible with their man responsibility, in order to be more effective and efficient in their contribution to reach the organization's goal. In reality, there are many organization which have employee empowerment fail to get the optimal result because they are not concent to skill, ability, knowledge and attitude of the employees and of course it will affect to the result of the empowerment itself. Besides, the level of the employees and certain condition are needed such as structure and culture support in order to reach an optimal result of this concept's implementation. However, it does not mean if all conditions above are being satisfied then empowering will be success, because this implementation means there is a process of change that should be done by the employees theirselves. To change the employees' attitude is not an easy thing. For those things the change in mindset of the employees should be done appropriately, so that with this empowering mindset will make the implementation of empowerment become easier.